Mitochondrial Kinase Signaling for Cardioprotection - Boengler, Kerstin; Eickelmann, Chantal; Kleinbongard, Petra; Justus Liebig University Giessen (My University, 2024)
Myocardial ischemia/reperfusion injury is reduced by cardioprotective adaptations such as local or remote ischemic conditioning. The cardioprotective stimuli activate signaling cascades, which converge on mitochondria and maintain the function of the organelles, which is critical for cell survival. The signaling cascades include not only extracellular molecules that activate sarcolemmal receptor-dependent or -independent protein kinases that signal at the plasma membrane or in the cytosol, but also involve kinases, which are located to or within mitochondria, phosphorylate mitochondrial target proteins, and thereby modify, e.g., respiration, the generation of reactive oxygen species, calcium handling, mitochondrial dynamics, mitophagy, or apoptosis. In the present review, we give a personal and opinionated overview of selected protein kinases, localized to/within myocardial mitochondria, and summarize the available data on their role in myocardial ischemia/reperfusion injury and protection from it. We highlight the regulation of mitochondrial function by these mitochondrial protein kinases.
Keywords: ddc:610